THE RELATIONSHIP INTEREST AND LEARNING MOTIVATION WITH LEARNING RESULTS STUDENT OF THE TENTH GRADE TKR A SMK KARSA MULYA PALANGKA RAYA ACADEMIC YEAR 2016/2017 - Lancing Mas Kaliyono; Jhonni Rentas Duling (Jurusan Pendidikan Teknologi Dan Kejuruan, 2019)
The main case in this research is influenced many factors that effecting student learning outcomes including interest and motivation factor due to have an important role in determining student's success. This research is aimed to know the relation of interest and motivation to student learning achievements at SMK Karsa Mulya Palangka Raya. The method used in this study is quantitative research using correlation research approach to find the relationship of interest and motivation to investigate the learning outcomes. The sample in this research is the students of the tenth grade TKR A with the total number at about 34 students. This sampling technique is using purposive sampling which technique of taking based on certain considerations. Data collection method of interest and motivation is taken from the questionnaire while the results of learning data collected from test block test. From the normality test results obtained that the data of interest and learning motivation on student learning outcomes normally distributed. Data analysis is using simple correlation and multiple correlation. The result showed that there was a correlation between interest to learning result with correlation number 0.83 as strong category, then there was correlation between learning motivation toward learning result with correlation number 0,82 as strong category. There was a correlation between interest and motivation to learning outcomes with correlation number 0.88 as strong category. All in all, interest and motivation in the learning outcomes have been argued that there is essential correlation to student academic performance.